Modeling and inverse problems in the presence of uncertainty - Banks, H. T. (Harvey Thomas), 1940-; Thompson, W. Clayton (Monographs and research notes in mathematics., 2014)
Modeling and Inverse Problems in the Presence of Uncertainty collects recent research-including the authors' own substantial projects-on uncertainty propagation and quantification. It covers two sources of uncertainty: where uncertainty is present primarily due to measurement errors and where uncertainty is present due to the modeling formulation itself. After a useful review of relevant probability and statistical concepts, the book summarizes mathematical and statistical aspects of inverse problem methodology, including ordinary, weighted, and generalized le.